Interferon-tau regulates the PGE2/PGF2α ratio via ISG15 in the goat corpus luteum during early pregnancy - Chunmei Shang; Haokun Liu; Zuhui Li; Yuanmeng Mou; Chenling Fan; Shan Liu; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Pore-scale heat transfer analysis in grain piles via X-ray CT and LBM - Xiaoliang Wang; Ying Zhou; Yaping Shi; Yanbo Hui; Ju Gao; Yihui Wang; Fan Yang (Journal of Food Engineering, 2026)

Prognostic factors and predictive modeling of in-hospital mortality among MDRO-positive inpatients: a retrospective cohort and GBD MICROBE study - Fan Jiang; Jian Li; Yahan Li; Yaping Yao; Ke Liu; Wei Dai; Hui Du (Antonie van Leeuwenhoek, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Non-sampling estimation of waste composition based on incineration flue gas pollutant fingerprints and machine learning approach - Yaping Qi; Pinjing He; Fan Lü; Hua Zhang (Journal of Environmental Sciences, 2026)

UiO-66 porous liquids with synergistic catalytic effects for promoting efficient CO2 conversion - Yaru Lu; Ruyu Bai; Dechao Wang; Yangyang Xin; Weirui Zhang; Fangfang Su; Zheng Dong; Wendi Fan; Yating Zhang; Fangli Yu; Xin Li; Yingying Zhou; et al. (Chemical Engineering Journal, 2026)

Synergistic defense in cotton: Lignin-mediated barriers and JA/ET signaling pathways against Verticillium wilt - Zhixin Liu; Yinpeng Zhang; Yaping Zhou; Baozhen Wang; Jiani Long; Mengyu Liao; Xiaoli Fan; Wenxuan Kang; Beibei Liu; Xuwu Sun (Plant Science, 2026)

Enhancing Kiwifruit (Actinidia spp.) Growth Through a Microbial Consortia in Alkali Soil - Xiao Shu; Yixiao Fan; Shuai Shen; Yaping Chen (Journal of Soil Science and Plant Nutrition, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

Future climate change exacerbates streamflow depletion in the Wei River Basin, China - Hongli Chen; Lijing Fan; Qiang Li; Yaping Wang; Dengfeng Liu; Fubo Zhao (Journal of Hydrology, 2025)

Testing and applying analytical depletion functions for multiple pumping wells in two hydrogeological landscapes - Lijing Fan; Hongli Chen; Qiang Li; Kunpeng Li; Yaping Wang (Journal of Hydrology, 2025)

Bioreduction-assisted synthesis of Co nanoclusters for selective singlet oxygen generation in ciprofloxacin degradation - Yuning Fan; Wenqian Zhang; Yaping Geng; Jiangjun Lin; Yefei Su; Kai Teng; Jiajie wu; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2025)

Unraveling the chrono-regulatory function of PhoP in nitrogen metabolism: A multi-scale engineering framework aimed at optimizing the synthesis of poly-γ-glutamic acid in Bacillus licheniformis - Qing Zhang; Shisi He; Zhihao Zhu; Fangzhou Cheng; Yaping Jin; Wanying Zhu; Fan Yang; Yaozhong Chen; Mengyuan Zhang; Xin Li; Dongbo Cai; Shouwen Chen (Chemical Engineering Journal, 2025)

Corrigendum to “Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption” [Chem. Eng. J. 500 (2024) 156655] - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2025)

The diurnal variation characteristics of warm season precipitation in Chongqing from 2011 to 2021 - Yingying Zhou; Yan Zhang; Chengzhi Deng; Qu Guo; Yaping Zhang; Yi Liu; Hong Zhang; Tingting Liu; Fan Xia (Theoretical and Applied Climatology, 2025)

Hyaluronan-decorated CuO2-doxorubicin nanodot clusters for targetedly sensitizing cuproptosis in breast cancer via a three-pronged strategy - Junmin Qian; Abdalrheem Jarelnaby Musa Aldai; Weijun Xu; Taibing Wang; Kunkun Zhao; Yaping Wang; Jingjing Fan; Aili Suo (Carbohydrate Polymers, 2025)

Detection of small foreign objects in Pu-erh sun-dried green tea: An enhanced YOLOv8 neural network model based on deep learning - Zejun Wang; Shihao Zhang; Yaping Chen; Yuxing Xia; Houqiao Wang; Ronghua Jin; Chun Wang; Zongpei Fan; Yuefei Wang; Baijuan Wang (Food Control, 2025)

How does high hydrostatic pressure treatment improve the esterification of quinoa (Chenopodium quinoa Willd.) starch? - Yaping Yin; Yongliang Zhuang; Liping Sun; Ying Gu; Gaopeng Zhang; Xuejing Fan; Yangyue Ding (Food Chemistry, 2025)

High lead-tolerant mutant Bacillus tropicus AT31-1 from rhizosphere soil of Pu-erh and its remediation mechanism - Qiang Li; Wenxia Yuan; Xiujuan Deng; Yaping Chen; Limei Li; Lijiao Chen; Raoqiong Che; Wei Huang; Yamin Wu; Chun Wang; Zejun Wang; Miao Zhou; et al. (Bioresource Technology, 2025)

Porous liquids based on UiO-66@SiO2 through the strategy of growing an ultrathin silica layer for CO2 selective separation - Zhaodi Wang; Yangyang Xin; Wendi Fan; Zheng Dong; Dechao Wang; Yaping Zheng; Yahong Xu (Chemical Engineering Journal, 2024)

Porous liquids based on ZIF-67@ZIF-8 through the strategy of interface layer reconstruction for CO2 selective sorption - Jiadi Li; Yangyang Xin; Zheng Dong; Baolu Cui; Zhiye Du; Jingwen Wang; Libing Qian; Shuangshuang Long; Zicheng Wei; Wendi Fan; Jinwen Fan; Yunpan Ying; et al. (Chemical Engineering Journal, 2024)

The nature of synergy effects between VO and TiO2 in low temperature NH3-SCR reaction - Yingying Jin; Jiaying Li; Kaihao Fan; Yong Chen; Yaping Yang; Xuesong Liu (Journal of Environmental Chemical Engineering, 2024)

A novel “pore-carrier transfer” strategy for preparation of porous liquids toward efficient CO2 capture - Yangyang Xin; Dechao Wang; Weirui Zhang; Fangfang Su; Jing Zhang; Yisong Liu; Wendi Fan; Xiaoqian Li; Libing Qian; Dongdong Yao; Yaping Zheng (Chemical Engineering Journal, 2024)

Synthesis of P-Rich Carbon Quantum Dots for Sensitive Fluorescent Detection of 2-Methylimidazole - Zhengyuan Dai; Hao Liu; Xuyuan Sun; Ying Wang; Jie Fan; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Seasonal dynamics, tidal influences, and anthropogenic impacts on microplastic distribution in the Yangtze River estuary: A comprehensive characterization and comparative analysis - Panfeng Wu; Yuchuan Fan; Xinxin Zhang; Wei Wu; Zaifeng Zhang; Yaping Wu; Jingyi Wang; Jing Xu; Tianming Chen; Bin Gao (Journal of Hazardous Materials, 2024)

Super absorbent resilience antibacterial aerogel with curcumin for fresh pork preservation - Fangqu Wang; Zipeng Xu; Lin Chen; Ziyan Qiao; Yayun Hu; Xiaojing Fan; Yaping Liu; Zhuangli Kang; Feng Huang; Minyi Han; Huijuan Yang; Xianchao Feng (Food Control, 2024)

Chemically tailored molecular surface modification of bamboo pulp fibers for manipulating the electret performance of electret filter media - Chunxia Pang; Huanhuan You; Sijie Lei; Fan Su; Lili Liang; Zhanguo Li; Xiaoyan Lin; Yaping Zhang; Hao Zhang; Xunhai Pan; Yang Hu (Carbohydrate Polymers, 2024)

Effects of elevated CO2 and spinetoram on the population fitness and detoxification enzymes activities in Frankliniella occidentalis and F. intonsa - Zongfang Fan; Yaping Chen; Rui Fan; Bin Chen; Lei Qian; Furong Gui (Journal of Pest Science, 2024)

Selective recovery of lithium from high-aluminum fly ash by using alkali-dissolution-assisted HBTA–TOPO synergistic extraction - Mingfei Xing; Fan Zhang; Pengyong Zheng; Yaping Wang; Li Zhao; Chuanyang Xu (Journal of Cleaner Production, 2024)

Tea polyphenols coated sodium alginate-gelatin 3D edible scaffold for cultured meat - Xiaohong Chen; Linzi Li; Lin Chen; Wei Shao; Yan Chen; Xiaojing Fan; Yaping Liu; Changbo Tang; Shijie Ding; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Simple and efficient strategy for α-MnO2/C by in-situ synthesis and its performance for degrading urea process wastewater - Yanli He; Shuguang Shen; Ying Wang; Chenyuan Guo; Yaping Yuan; Yaru Fan; Lili Zhang; Yuyan Song (Journal of Environmental Chemical Engineering, 2023)

Assessing Spatio-Temporal Variability of Soil Phosphorus in Different Cotton-Based Cropping Systems Using Geo-Statistics - Li Teng; Xiong Shiwu; Wang Zhanbao; Li Xiaofei; Han Yingchun; Wang Guoping; Lei Yaping; Feng Lu; Yang Beifang; Zhi Xiaoyu; Fan Zhengyi; Li Yabing (Journal of Soil Science and Plant Nutrition, 2023)

Visualize intracellular β-galactosidase using an asymmetric near-infrared fluorescent probe with a large Stokes shift - Shijun Chen; Xiaodong Ma; Haijie Wang; Lin Wang; Yuanyuan Wu; Yaping Wang; Yiyi Li; Wenkang Fan; Caoyuan Niu; Shicong Hou (Analytica Chimica Acta, 2023)

Rare earth element recovery and aluminum-rich residue production from high alumina fly ash by alkali pre-desilication enhance the mechanochemical extraction process - Mingfei Xing; Xiaofang Wu; Zixin Li; Fan Zhang; Yaping Wang; Li Zhao (Process Safety and Environmental Protection, 2023)

Suppression mechanism of L-lysine on the Epigallocatechin-3-gallate-induced loss of myofibrillar protein gelling potential - Mengyuan Wang; Jingchao Kang; Lin Chen; Gongchen He; Yaping Liu; Xiaojing Fan; Xin Lv; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Influencing mechanism and hydrogeological implications of water level fluctuation of lakes in the northern Qaidam Basin, Qinghai-Tibet Plateau - Yaping Cheng; Qishun Fan; Tianyuan Chen; Haotian Yang; Qingkuan Li; Chunmei Han (Journal of Oceanology and Limnology, 2023)

Design of bifunctional TiO2-SSZ-13 mixed supports for potassium-resistant vanadia catalysts for NH3-SCR - Xuesong Liu; Yaping Yang; Jiaying Li; Yang Gao; Kaihao Fan; Yanghui Wang; Xintao Xu; Letong Yang; Xiaodong Wu (Fuel, 2023)

The nitrogen footprint and reactive nitrogen reduction potential of cotton production in China - Weibin Huang; Fengqi Wu; Zhenggui Zhang; Yongming Meng; Jian Wang; Qinqin Li; Yingchun Han; Lu Feng; Xiaofei Li; Guoping Wang; Yaping Lei; Zhengyi Fan; et al. (Journal of Cleaner Production, 2023)

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Genetic diversity and structure of a core collection of Huangqi (Astragalus ssp.) developed using genomic simple sequence repeat markers - Fanshu Gong; Yaping Geng; Pengfei Zhang; Feng Zhang; Xinfeng Fan; Yaling Liu (Genetic Resources and Crop Evolution, 2023)

Longitudinal residual circulation in the South Passage of Yangtze Estuary: Combined influences from runoff, tide and bathymetry - Lifen Zhang; Zuosheng Yang; Fan Zhang; Zhanhai Li; Yaping Wang; Shu Gao (Science China Earth Sciences, 2021)

Cotton seedling drought tolerance is improved via salt preconditioning - Rong Fan; Xiujuan Su; Yaping Guo; Fenglei Sun; Yanying Qu; Quanjia Chen (Protoplasma, 2021)

Conditional Deletion of Foxg1 Alleviates Demyelination and Facilitates Remyelination via the Wnt Signaling Pathway in Cuprizone-Induced Demyelinated Mice - Fuxing Dong; Dajin Liu; Feiyu Jiang; Yaping Liu; Xiuxiang Wu; Xuebin Qu; Jing Liu; Yan Chen; Hongbin Fan; Ruiqin Yao (Neuroscience Bulletin, 2021)
The massive loss of oligodendrocytes caused by various pathological factors is a basic feature of many demyelinating diseases of the central nervous system (CNS). Based on a variety of studies, it is now well established that impairment of oligodendrocyte precursor cells (OPCs) to differentiate and remyelinate axons is a vital event in the failed treatment of demyelinating diseases. Recent evidence suggests that Foxg1 is essential for the proliferation of certain precursors and inhibits premature neurogenesis during brain development. To date, very little attention has been paid to the role of Foxg1 in the proliferation and differentiation of OPCs in demyelinating diseases of the CNS. Here, for the first time, we examined the effects of Foxg1 on demyelination and remyelination in the brain using a cuprizone (CPZ)-induced mouse model. In this work, 7-week-old Foxg1 conditional knockout and wild-type (WT) mice were fed a diet containing 0.2% CPZ w/w for 5 weeks, after which CPZ was withdrawn to enable remyelination. Our results demonstrated that, compared with WT mice, Foxg1 -knockout mice exhibited not only alleviated demyelination but also accelerated remyelination of the demyelinated corpus callosum. Furthermore, we found that Foxg1 knockout decreased the proliferation of OPCs and accelerated their differentiation into mature oligodendrocytes both in vivo and in vitro . Wnt signaling plays a critical role in development and in a variety of diseases. GSK-3β, a key regulatory kinase in the Wnt pathway, regulates the ability of β-catenin to enter nuclei, where it activates the expression of Wnt target genes. We then used SB216763, a selective inhibitor of GSK-3β activity, to further demonstrate the regulatory mechanism by which Foxg1 affects OPCs in vitro . The results showed that SB216763 clearly inhibited the expression of GSK-3β, which abolished the effect of the proliferation and differentiation of OPCs caused by the knockdown of Foxg1 . These results suggest that Foxg1 is involved in the proliferation and differentiation of OPCs through the Wnt signaling pathway. The present experimental results are some of the first to suggest that Foxg1 is a new therapeutic target for the treatment of demyelinating diseases of the CNS.

Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field * - Liyuan Liu; Fangfang Xing; Yabing Li; Yingchun Han; Zhanbiao Wang; Xiaoyu Zhi; Guoping Wang; Lu Feng; Beifang Yang; Yaping Lei; Zhengyi Fan; Wenli Du (Irrigation and Drainage, 2020)
The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely.

Assessing the effects of oyster/kelp weight ratio on water column properties: an experimental IMTA study at Sanggou Bay, China - Jinghui Fang; Jianguang Fang; Qionglin Chen; Yuze Mao; Zengjie Jiang; Meirong Du; Yaping Gao; Fan Lin (Journal of Oceanology and Limnology, 2020)

Simulation of oyster ecological carrying capacity in Sanggou Bay in the ecosystem context - Yaping Gao; Jianguang Fang; Fan Lin; Fengxue Li; Wenhao Li; Xiaoqin Wang; Meirong Du; Jinghui Fang; Weiwei Jiang; Hui Liu; Yitao Zhang; Junwei Wang; et al. (Aquaculture International, 2020)

Sodium-induced solid-phase hydrogenation of carbon dioxide to formate by mechanochemistry - Dunfan Zhou; Meng Yu; Yaping Fan; Zhenyu Wang; Guoju Dang; Quansheng Zhang; Jingying Xie (Environmental Chemistry Letters, 2020)

Simulation of Yesso scallop, Patinopecten yessoensis, growth with a dynamic energy budget (DEB) model in the mariculture area of Zhangzidao Island - Weiwei Jiang; Fan Lin; Meirong Du; Jianguang Fang; Jinghui Fang; Yaping Gao; Xiaoqin Wang; Fengxue Li; Shipeng Dong; Xing Hou; Zengjie Jiang (Aquaculture International, 2020)

Response of Yesso scallop Patinopecten yessoensis to acute temperature challenge: physiological and biochemical parameters - Weiwei Jiang; Meirong Du; Jianguang Fang; Yaping Gao; Yuze Mao; Qionglin Chen; Fan Lin; Zengjie Jiang (Journal of Oceanology and Limnology, 2019)

Probiotics decrease depressive behaviors induced by constipation via activating the AKT signaling pathway - Nana Xu; Wenting Fan; Xiaoyan Zhou; Yaping Liu; Ping Ma; Suhua Qi; Bing Gu (Metabolic Brain Disease, 2018)

Olfactory-ensheathing cells promote physiological repair of injured recurrent laryngeal nerves and functional recovery of glottises in dogs - Hongyi Liu; Yu Pu; Yaping Xu; He Xu; Huanhai Liu; Yin Cheng; Weihua Xu; Xiaoping Chen; Jingping Fan (Molecular and Cellular Biochemistry, 2018)

Erratum to: Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features - Jing Zhang; Tomasz Gambin; Bo Yuan; Przemyslaw Szafranski; Jill A. Rosenfeld; Mohammed Al Balwi; Abdulrahman Alswaid; Lihadh Al-Gazali; Aisha M. Al Shamsi; Makanko Komara; Bassam R. Ali; Elizabeth Roeder; et al. (Human Genetics, 2017)

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features - Jing Zhang; Tomasz Gambin; Bo Yuan; Przemyslaw Szafranski; Jill A. Rosenfeld; Mohammed Al Balwi; Abdulrahman Alswaid; Lihadh Al-Gazali; Aisha M. Al Shamsi; Makanko Komara; Bassam R. Ali; Elizabeth Roeder; et al. (Human Genetics, 2017)

Luman recruiting factor is involved in stromal cell proliferation during decidualization in mice - Xiao Li; Pengfei Lin; Fenglei Chen; Nan Wang; Fan Zhao; Aihua Wang; Yaping Jin (Cell and Tissue Research, 2016)

DNA barcoding reveals commercial fraud related to yak jerky sold in China - Yunyu Wang; Kai He; Long Fan; Yushui Wang; Shifang Wu; Robert W. Murphy; Wenzhi Wang; Yaping Zhang (Science China Life Sciences, 2016)

A Rosa canina WUSCHEL-related homeobox gene, RcWOX1, is involved in auxin-induced rhizoid formation - Bin Gao; Chao Wen; Lusheng Fan; Yaping Kou; Nan Ma; Liangjun Zhao (Plant Molecular Biology, 2014)

Mutation screen and RNA analysis disclose the changed splicing of the E-cadherin transcription in gastric cancer - Xiaowei Li; Yafan Gao; Yiyuan Pan; Yan Pan; Lifeng Wang; Nong Xiao; Qiong He; Yimei Fan; Yaping Wang (Familial Cancer, 2013)

Spontaneous uptake of exogenous DNA by goat spermatozoa and selection of donor bucks for sperm-mediated gene transfer - Yongju Zhao; Mingju Yu; Lingbin Wang; Yaofeng Li; Jingsheng Fan; Qian Yang; Yaping Jin (Molecular Biology Reports, 2012)

Influence of Eight Unclassified Missense Variants of the MLH1 Gene on Lynch Syndrome Susceptibility - Yimei Fan; Jinyun Chen; Wei Wang; Puyuan Wu; Wenxian Zhi; Binshuang Xue; Wanfen Zhang; Yaping Wang (Biochemical Genetics, 2012)

Population genetic analysis of 6 Y-STR loci in Chinese northwestern Qinchuan yellow cattle breed - Yaping Xin; Linsen Zan; Yongfeng Liu; Hongyu Liu; Wanqiang Tian; Yueyuan Fan; Lei Huang (Molecular Biology Reports, 2010)

The application of geostatistics in grain size trend analysis: A case study of eastern Beibu Gulf - Fei Ma; Yaping Wang; Yan Li; Changjiang Ye; Zhiwei Xu; Fan Zhang (Journal of Geographical Sciences, 2010)